Manajemen Lingkungan Madrasah Perspektif Al-Qur’an dan Hadits - Wahyuni, Amalia Desy; Zahid, Moh. (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
The research intends to examine the idea of madrasah environmental management through the lens of the Qur’an and Hadith as a means to establish a clean, healthy and religious educational setting. This research demonstrates that management extends beyond administration, encompassing environmental factors that facilitate the execution of education. This research emplys a qualitative method through a literature review strategy, which involves gathering and examining literature from pertinent primary and secondary sources, including verses from the Qur’an, Hadith of the prophet and scholarly references concerning environmental management and Islamic education. The study’s findings indicate that the Qur’an clearly emphasizes the significance of preserving and maintaining nature as a divine command from Allah SWT, as expressed in its verses. In the meantime, tha hadiths of the prophet highlight the importance of hygiene, community responsibility and the banning of environmental pollution. The aplication of these principles within madrasah involves creating eco-friendly policies, promoting a clean lifestyle, and instilling ecological character education grounded in Islamic values. Therefore, the environmental management of madrasahs is not just practical but also theological and ethical, serving as a means to embody islamic values in daily life.